Manifestasi Pelestarian Seni Budaya Sunda Ditengah Pandemi Covid-19 - Ai Novitasari; Mohamad Subur Drajat (UNISBA Press, 2022)
Abstract. Preservation of Sundanese culture and arts is the main focus of LSBS Unisba in carrying out an activity because it is one of the objectives of the Sundanese Cultural Arts Environment, the preservation of Sundanese culture and arts also needs to be done so that new generations are not blind to culture, especially Sundanese. With the existence of culture, norms and customs in society, it is much more attached or it can be said that society can be more prosperous with a good culture, while in art everyone can use it as a means of self-expression. That's what made the writer interested in taking the title